Obwód Kaliningradzki FR w stosunkach unijno-rosyjskich - Kotowicz, Wojciech (Wydział Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2011)
Due to its history and isolation from the proper territory of the Russian Federation since 1991, the Kaliningrad Oblast exhibits unique features in comparison to other parts of the country. This territory has been one of the key factors in relations between Russia and the European Union in terms of Russian domestic and foreign policy. Poland and Lithuania joining the European Union in 2004 transformed the Kaliningrad Oblast into an enclave inside the European Union and made it a ‘double periphery’. On account of its geo-political location the Kaliningrad Oblast was to become ‘a bridge spanning East and West’, ‘Russia’s gateway to Europe’ and ‘a pilot region for Russia-EU cooperation’. The paper shows the position and role the Kaliningrad Oblast plays in Russia-EU cooperation and outlines its prospects for development.
The Kaliningrad Oblast of the Russian Federation in EU-Russian relations